SAMPLING DENSITY INTERFERENCE ON SOIL FEATURE SPATIALIZATION BY MAPPING CAMBISOL UNIT TAXONOMY - SOUZA, Luiz Claudio de Paula; OLIVEIRA JUNIOR, Jairo Calderari de (Scientia Agraria, 2010)
In an area that have approximately 10 ha the B horizon were sampled on a regular grid with 133 points 30 m distant to each other (30x30) and another with 77 points 60 m distant to each other (60x60). Texture, exchangeable Ca+2, Mg+2, K+, H+, Al+3, H + Al, organic carbon were determined. The classic statistic and geoestatistics analyses were used to identify the variability structure, taking a model for further interpolation. These attributes were interpolated by kriging method, then applied the map algebra and Boolean analysis for identify the diagnostic horizon as well the others taxonomy classes until the specific level group.It was possible to identify by semivariogram analysis that values of proportion, nugget, range, r2 and RSS were near each other in the both grids, with the exception of H + Al.In application of taxonomy discretion, the CXa and CXvd units were not identified in the reduced grid. Even though the CXbd was identified in both grids, it was different in the spatial distribution and expression of area.